The Consequences of Training and Competition to the Musculoskeletal System in Ultramarathon Runners: A Narrative Review - Partyka, Alicja; Waśkiewicz, Zbigniew (Frontiers in Physiology, 2021)
Ultramarathons are becoming increasingly popular every year, leading to more and more publications focusing on athletes of these endurance events. This paper summarizes the current state of knowledge on the effects of ultramarathons on the motor system. Various studies have attempted to answer questions about negative and positive effects on the musculoskeletal system, common injuries, optimal strategies, and regeneration. Considering the increasing number of ultramarathon athletes, the discoveries may have practical applications for a multitude of experts in the field of sports medicine, as well as for the athletes themselves. Acute locomotor system changes in runners as assessed by locomotor biomarkers are reversible, and may be asymptomatic or painful. Injuries suffered by runners largely allow them to finish the competition and are usually overlooked. Regeneration, including regular massage and the use of supporting techniques, allows for faster convalescence. This publication is meant to be an important source of knowledge for people associated with this discipline.